A Study among Chemical Suicidal Victims: Situation Analysis (Delta Medical College Journal, 2024)
Background: Suicide by poisoning is the act of intentionally killing oneself by using various chemical substances and it is the most common and widely used method in developing countries like Bangladesh. Objective: The objectives of this study were to find out the socio-demographic characteristics and possible reasons among the chemical suicidal victims. Materials and method: This was a descriptive type of cross-sectional study, held in the Morgue of department of Forensic Medicine of Dhaka Medical College (DMC), Dhaka, Bangladesh, from July 2016 to June 2018. Victims were selected purposively according to the availability in the morgue of Dhaka MedicalCollege. Data were collected from the relatives of the victims and the verbal consent of the doctors who performed autopsy at DMC morgue. Results: A total of 50 victims of suicide using chemical substances as revealed by autopsy findings from the DMC morgue were enlisted in this study. Victims of suicide not using chemicals were excluded from this study. Half (50.0%) of the suicidal deaths by poisoning cases were aged 20 or below. Majority (66.0%) of the victims was male. Organophosphorus compound was found in 58.0% cases, followed by diazepam (8.0%) and barbiturates (4.0%), after receiving chemical analysis report. Conclusion: Pesticides are the most commonly used suicidal agent particularly in low and middle-income countries like ours. So, social awareness regarding this issue is very much needed.Delta Med Col J. Jan 2021;9(1):23-27